Potential anticancer effects of Peganum harmala in human papillomavirus-related cervical and head and neck cancer cells - Muddather, Hiba F.; Nasibova, Tohfa; Szebeni, Gábor J.; Gémes, Nikolett; Bózsity, Noémi; Minorics, Renáta; Garayev, Eldar; Orhan, Ilkay Erdogan; Herbette, Gaëtan; Schelz, Zsuzsanna; Hohmann, Judit; Zupkó, István (Frontiers in Pharmacology, 2025)
BackgroundP. harmala L (P. harmala) has a longstanding role in ethnomedical treatments. Its reported anticancer effects have led to increased research interest; however, its antineoplastic properties on cervical and head and neck (HN) cancer cells need further investigation. In this study, we investigated P. harmala’s antineoplastic effects on HPV-infected cervical and HN cancer cell lines.MethodsThe crude extract derived from multiple plant parts and isolated β-carboline alkaloids was tested on several human neoplastic cell types using the MTT-based analysis. Apoptosis was examined by fluorescent double staining, Annexin V-Alexa 488–propidium iodide labeling, and caspase-3 assays. Moreover, flow cytometry was employed to explore the cell cycle progression alterations, while the tubulin polymerization assay assessed influences on microtubule dynamics. The antimetastatic property was investigated by wound healing and transwell invasion assays to explore the impact on cellular motility and invasiveness, respectively.ResultsThe IC50 values were calculated and examined relative to non-malignant fibroblasts to assess selective toxicity. The root extract demonstrated the most substantial growth-inhibitory effect among the tested extracts. Harmine, one of the isolated bioactive alkaloids, showed a substantial effect, with inhibitory concentrations between 6.05 and 27.85 µM. Apoptosis induced by harmine was confirmed through cellular morphological appearance, flow cytometric evaluations, and caspase-3 activation. Assessment of the cell cycle demonstrated that harmine disrupted cell cycle progression, particularly increasing the apoptotic sub-G1 and G2/M phase populations. Moreover, it revealed the ability to stabilize microtubules. Our findings showed that harmine and the root extract significantly reduced cell migration. Furthermore, harmine was found to have anti-invasive properties.ConclusionThese findings showed potential harmine antiproliferative and antimetastatic activities, indicating its potential for further research in developing natural therapeutic agents.